Pembuatan Hantaran Pengantin Pada Ibu PKK Kelurahan Pekan Tanjung Morawa - Hasibuan, Elfi Husnita; Meilasari, Retno Desti Dwi; Butar Butar, Khairunnisa (-, 2025)
Exploring Potential and Seeking Opportunities, especially from the economic sector and the creative industry, must be carried out by upgrading capabilities and skills, to be remanaged. One of them is through skills training on making handycraft (bridal gifts) from multi-purpose materials for PKK women in Pekan Tanjung Morawa village, Deli Tengah Regency. With the aim that the community is able to find and process the Multipurpose Materials that we have in our lives to become creative and innovative products that have new benefits and selling value. The training method used is two-way communication (instructor and participant) by conducting demonstrations, practices and evaluations. The teaching materials used are handouts and presentation media (PPT), Leaflet, LCD, In focus, Sound System. Meanwhile, the tools and materials used are Towels, Satin Ribbons, Flannel Fabrics, Scissors, Glue Guns, Wooden Scissors, and Hand Needles, as well as sewing thread. The result of this activity is the enthusiasm of the trainees / PKK mothers in making handycrafts by looking at the results of practice based on their respective ideas. With the product results and the positive response from this activity, it can be seen that the interest of the PKK trainees / women in redeveloping products from this multi-purpose material with follow-up meetings / activities.